2016
DOI: 10.1016/j.bcp.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor (AHR) regulation of L-Type Amino Acid Transporter 1 (LAT-1) expression in MCF-7 and MDA-MB-231 breast cancer cells

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that is regulated by environmental toxicants that function as AHR agonists such as 2,3,7,8 tetrachlorodibenzo-p-dioxin (TCDD). L-Type Amino Acid Transporter 1 (LAT1) is a leucine transporter that is overexpressed in cancer. The regulation of LAT1 by AHR in MCF-7 and MDA-MB-231 breast cancer cells (BCCs) was investigated in this report. Ingenuity pathway analysis (IPA) revealed a significant association between TCDD-regulated genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…There may also be other mechanisms through which the AhR promotes cell proliferation and survival. For example, the AhR can increase cell numbers by regulating the expression of L‐type amino acid transporter 1 (LAT‐1), which promotes the absorption of amino acids . TCDD promotes palatal epithelial cell proliferation and survival via activating the MAPK pathway .…”
Section: Discussionmentioning
confidence: 99%
“…There may also be other mechanisms through which the AhR promotes cell proliferation and survival. For example, the AhR can increase cell numbers by regulating the expression of L‐type amino acid transporter 1 (LAT‐1), which promotes the absorption of amino acids . TCDD promotes palatal epithelial cell proliferation and survival via activating the MAPK pathway .…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that LAT1 is an aryl hydrocarbon receptor (AHR) target gene and that reducing AHR or LAT1 with short interfering RNA (siRNA) reduces the proliferation of MCF7 and MDA-MB-231 breast cancer cells [9]. Dioxins are widespread environmental toxicants that bind AHR with high affinity.…”
Section: Lat1 and Ahrmentioning
confidence: 99%
“…These studies generally found that suppression of ASCT2 led to detrimental effects on glutamine transport, mTORC1 signaling, proliferation, and cell cycle progression. LAT1 has also been targeted with shRNA and small molecular inhibitors in a broad spectrum of cancers including esophageal squamous cell carcinoma [ 24 ], gastric cancer [ 25 ], cholangiocarcinoma [ 26 ], breast cancer [ 27 ], ovarian cancer [ 28 ], and endometrial carcinoma [ 29 ], among others. Like ASCT2, these studies generally found that the suppression of LAT1 led to detrimental effects on leucine transport, mTORC1 signaling, proliferation, and cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%